IMPROVEMENT OF TRADITIONAL BALINESE "ONG" TEA-MAKING PROCESS TO EXTEND SHELF LIFE TO SUPPORT ECOTOURISM IN BANJAR LANTANGIDUNG, GIANYAR, BALI - Sudiarta, I Wayan; Ni Luh Putu Putri, Setianingsih; Pratiwi, Ni Luh Putu Yumi Mega; Rustini, Ni Made; Kusuma, David Ali Jaya; Mulia, Komang Oki Budi (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
“Ong” tea contains vitamins B1, B2, B6, B12, folic acid, and vitamin C, in addition to several essential amino acids, organic acids, minerals, vitamins, amino acids, and active polyphenol compounds, and various important enzymes that have many benefits for the body. “Ong” tea is a type of probiotic drink produced from the tea fermentation process. The bacteria contained in SCOBY (Symbiotic Consortium of Bacteria and Yeast) are Acetobacter xylinum bacteria. The purpose of implementing the activities proposed in the training to improve the process of making “Ong” tea through PKM activities is to ensure that the people of Br. Lantangidung, Batuan, Sukawati have the skills and insight to manage local natural resources and have an entrepreneurial spirit so that they can open up business opportunities related to the conditions of the Batuan Village area. Improving product quality, expanding marketing reach, and using more hygienic and modern packaging techniques are also important. Thus, it is hoped that Balinese “ong” tea can become a superior product that can improve the community's economy and support the development of ecotourism in Banjar Lantangidung